The des(1-6)antennapedia homeodomain: comparison of the NMR solution structure and the DNA-binding affinity with the intact Antennapedia homeodomain. - Qian, Y Q (1994)
The nuclear magnetic resonance (NMR) solution structure of an N-terminally truncated mutant Antennapedia homeodomain, des(1-6)Antp(C39S), has been determined from 935 nuclear Overhauser effect upper distance constraints and 148 dihedral angle constraints by using the programs DIANA and OPAL. Twenty conformers representing the solution structure of des(1-6)Antp(C39S) have an average root-mean-square distance relative to the mean coordinates of 0.56 A for the backbone atoms of residues 8-59. Comparison with the intact Antp(C39S) homeodomain shows that the two proteins have identical molecular architectures. The removal of the N-terminal residues 1-6, which are flexibly disordered in the intact homeodomain, causes only strictly localized structure variations and does not noticeably affect the adjoining helix I from residues 10-21. The DNA-binding constant of des(1-6)Antp(C39S) is approximately 10-fold reduced relative to the intact Antp(C39S) homeodomain, which can now be attributed to the absence of the previously reported contacts of the N-terminal polypeptide segment of the intact Antp(C39S) homeodomain with the minor groove of the DNA duplex.